2014
DOI: 10.1007/s13337-014-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 expression in shrimp Litopenaeus vannamei in response to IHHNV and WSSV infection

Abstract: The effects of environmental changes, on nontarget organisms may impact and bring consequences at the molecular level in marine organisms. There is a lack of data supporting the hypothesis according to which environmental stress modulates the immune system, leading to an increased susceptibility to infectious agents in shrimps. The present study was focused on changes occurring in cellular defense proteins in Litopenaeus vannamei infected by virus infection hypodermal and hematopoietic necrosis (IHHNV) and whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Ding, Wang, Sun, Guo and Dong (2009) shrimp. Virus infection promoted changes in the expression of Hsp70 in Litopenaeus vannamei (Valentim-Neto, Moser, Fraga, & Marques, 2014). Transcription of LvHSP70 was induced in haemocytes and hepatopancreas of Litopenaeus vannamei after different bacteria injection (Zhou, Wang, He, Zheng, Wang, Xin, Liu, & Wang, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Ding, Wang, Sun, Guo and Dong (2009) shrimp. Virus infection promoted changes in the expression of Hsp70 in Litopenaeus vannamei (Valentim-Neto, Moser, Fraga, & Marques, 2014). Transcription of LvHSP70 was induced in haemocytes and hepatopancreas of Litopenaeus vannamei after different bacteria injection (Zhou, Wang, He, Zheng, Wang, Xin, Liu, & Wang, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis in the gill tissue of L . vannamei indicated that the expression of HSP70 was up-regulated by infecting the pathogens of white spot syndrome (WSSV) and hypodermal-hematopoietic necrosis (IHHNV) [127]. The mRNA and protein expression levels of HSP70 were observed highest in the heat-stress group of goats ( Capra hircus ) [128].…”
Section: Discussionmentioning
confidence: 99%
“…A heat shock protein 70 (Hsc70) was found to inhibit apoptosis induced by WSSV infection in hemocyte shrimp cells [51]. In shrimp P. vannamei, the expression of the Hsp70 gene was also reported altered after the WSSV infection [52,53], and intramuscularly injection of Hsp70 protein could significantly reduce mortality after WSSV infection [54]. As for the Hsp40 gene, its responses to viral infection have been reported in halibut Paralichthys olivaceus [55].…”
Section: Nimav-1_lva Genes Involved In Host-pathogen Interactionmentioning
confidence: 99%